Kosovo Country Economic Memorandum, November 2021 : Raising Firm Productivity - World Bank (World Bank, Washington, DC, 2022)
To boost economic growth and foster sustained formal job creation in Kosovo, igniting firm productivity is crucial. Based on detailed micro-data, this note examines the characteristics and recent evolution of firms in Kosovo, with particular attention to firm productivity. For the last decade, the landscape of firms in Kosovo has been dominated by microenterprises with low productivity, employment, and survival rates. Firm creation and growth,small firm density, average size, and the likelihood of survival are all low, which implies that there are severe constraints on private sector development. Kosovo’s firms are only tenuously linked to global markets and the country is lagging in the share of female-run companies. Positive and rising net job creation in 2015-18 was driven by higher formalization of jobs and the increasing size of incumbent firms, especially young small and medium enterprises (SMEs). Kosovo needs a multidimensional policy strategy to foster growth in firm productivity. Based on the study findings and the results of other notes prepared for Kosovo’s country economic memorandum (CEM), this note presents a policy strategy that targets the three main sources of firm productivity growth: (1) firm productivity (the within component); (2) market reallocation (the between component); and (3) firm dynamics (entry and exit). Section one examines the characteristics and recent dynamics of Kosovar firms. Section two analyzes the drivers and evolution of productivity, with emphasis on the links between productivity and access to credit. It also assesses the main barriers to productivity growth. Section three sheds light on how Coronavirus disease 2019 (COVID-19) has affected Kosovar firms. Section four concludes by discussing tentative policy implications of the analysis.